Do bilateral deficits in hop for distance performance occur concomitantly with bilateral movement differences in people with patellofemoral pain? A cross-sectional investigation with between-group and -limb comparisons - Waiteman, Marina C. [UNESP]; Batista, Natanael P.; Garcia, Micah C.; de Azevedo, Fábio M. [UNESP]; Bazett-Jones, David M. (Elsevier, 2025)
Background: People with patellofemoral pain (PFP) may have bilateral deficits in hop for distance test (SLHD) performance, whereas the worsening performance of the pain-free or less painful limbs suggests that bilateral movement differences may occur. While clinicians may not be aware of bilateral movement differences that may be employed during the clinical assessment of SLHD performance (e.g., excessive trunk flexion, lower knee, hip and ankle angles), their suboptimal investigation may overestimate function and favor long-term sequelae. Research question: Do people with PFP exhibit bilateral differences in trunk and lower limb movements as well as bilateral deficits in SLHD performance compared to pain-free controls? Methods: We captured three-dimensional motion of 26 adults with PFP and 22 controls during testing and calculated trunk and lower limb sagittal plane kinematics, total concentric and eccentric work, and hip, knee, and ankle work contributions during the jumping and landing phases of the SLHD. We also calculated vertical ground reaction forces during the landing phase and compared between-group and -limb differences using independent and paired t-tests. Results: People with PFP demonstrated bilateral deficits in SLHD performance (medium effects; p = .028–.050) and lower peak vertical ground reaction force values (medium-to-large effects; p = .006–.012) as compared to controls. No other between-group or -limb differences were identified. Significance: Bilateral deficits in SLHD performance seem to occur independently of movement differences in people with PFP, as they presented shorter distance but no differences in sagittal plane biomechanical patterns.
Keywords: Anterior knee pain; Biomechanics; Physical performance; Single-leg hop test